ER-to-Golgi Transport in HeLa Cells Displays High Resilience to Ca2+ and Energy Stresses - Thomas Rauter; Sandra Burgstaller; Benjamin Gottschalk; Jeta Ramadani-Muja; Helmut Bischof; Jesse C. Hay; Wolfgang F. Graier; Roland Malli (Cells, 2020)
One third of all human proteins are either transmembrane or soluble secretory proteins that first target the endoplasmic reticulum (ER). These proteins subsequently leave the ER and enter the Golgi apparatus via ER-Golgi intermediate vesicular structures. Live-cell imaging of cargos fused to fluorescent proteins (FPs) enables the high-resolution visualization and characterization of secretory transport processes. Here, we performed fluorescence time-lapse imaging to assess the Ca2+ and energy dependency of ER-to-Golgi transport in living HeLa cells, a cancer cell model which has been well investigated. Our data revealed that ER-to-Golgi transport remained highly efficient in the absence of ATP-generating substrates, despite clear reductions in cytosolic and mitochondrial ATP levels under these energy stress conditions. However, cell treatment with 2-deoxy-D-glucose (2-DG), which severely diminished subcellular ATP levels, abolished ER-to-Golgi transport. Interestingly, while 2-DG elevated cytosolic Ca2+ levels and reduced long-distance movements of glycosylphosphatidylinositol (GPI)-positive vesicles, robust short-term ER Ca2+ mobilizations, which strongly affected the motility of these vesicles, did not considerably impair ER-to-Golgi transport. In summary, we highlight that ER-to-Golgi transport in HeLa cells remains functional despite high energy and Ca2+ stress levels.